KAJIAN TEORI LIE PADA OSILATOR HARMONIS DAN BANDUL TERBALIK - , IRMAN SAID PRASTYO, Dr. rer. nat. Muhammad Farchani Rosyid ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The symmetry of simple mechanical systems problem has been studied in the framework of Lie theory. Two systems, i.e. harmonic oscillator and inverse pendulum, have been taken as concrete cases of the analysis. The analysis is applied to both systems by involving symmetry Lie group in order to obtain classical description. By using biinvariant metric, it can be shown that R 2 -manifold as phase space for both systems is a symplectic manifold that is also the coadjoint orbit of Heisenberg Lie group. Next, the dynamic of the system is given in the form of equation of motion through the application of the Hamiltonian equations.